Uganda : Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
This report summarizes the Annual Progress Report of Uganda on the Poverty Reduction Strategy Paper, which highlights the progress and outcomes of implementation of the Poverty Eradication Action Plan (PEAP) policies and programs. It provides assessments on achievements and problematic areas in implementing the PEAP as well as recommendations on the corrective measures to meet Uganda's poverty reduction targets. It also reviews governance and security, and discusses ways to increase the ability of the poor to raise their income, and to improve the quality of life of the poor.